Fool's gold why the Internet is no substitute for a library - Herring, Mark Y. 1952- (Jefferson, N.C. McFarland, 2007)
"This work skeptically explores the notion that the Internet will soon obviate any need for traditional print-based academic libraries, and makes a case for the library's staying power in the face of technological advancements"--Provided by publisher.
Caught in the Web -- Forget the needle. Can you just tell me which haystack? -- Weare18.com -- Footnotes? who needs them! -- Google über alles -- E-books to the rescue! -- The paperless revolution is complete! -- A mile wide and a mind-numbing inch deep -- The endgame : quo vadis?
Includes bibliographical references (p. 167-187) and index.
Keywords: Computer network resources -- Evaluation; Web sites -- Evaluation; Libraries -- Special collections|xElectronic books; Libraries and the Internet; Libraries and electronic publishing; Libraries -- Forecasting; Library science -- Forecasting; Electronic books -- Forecasting